Effectiveness of Low-Dose Aspirin in Preventing Pre-Eclampsia in High-Risk Pregnant Women: A Randomized Controlled Trial in Tertiary Care Hospitals - Aslam, Maham; Iqbal, Hira; Jabeen, Shumaila (Biological and Clinical Sciences Research Journal, 2025)
Pre-eclampsia is a leading cause of maternal and perinatal morbidity and mortality in Pakistan. Low-dose aspirin (LDA) has been identified as a promising preventive strategy for high-risk pregnancies when initiated early. This study aimed to evaluate the effectiveness of daily low-dose aspirin in preventing pre-eclampsia and improving maternal and neonatal outcomes in a tertiary care setting. Methods: This randomized controlled trial was conducted at a tertiary care hospital in Pakistan over six months (August 2024 to January 2025). A total of 86 high-risk pregnant women were randomly assigned to either the aspirin group (75 mg/day from 12–16 to 36 weeks of gestation) or the control group receiving routine antenatal care. Data on maternal blood pressure, proteinuria, and clinical outcomes were collected and compared. Perinatal outcomes were also recorded, including birth weight, gestational age at delivery, and NICU admission. Statistical analysis was performed using SPSS v26, with p < 0.05 considered significant. Results: Pre-eclampsia occurred in 13.9% of women in the aspirin group versus 34.9% in the control group (p = 0.02). Severe pre-eclampsia was significantly lower in the aspirin group (4.7% vs. 20.9%, p = 0.03). Rates of preterm delivery, low birth weight, and NICU admission were significantly reduced among aspirin users. Additionally, the intervention group better controlled systolic and diastolic blood pressures and proteinuria levels. Conclusion: Low-dose aspirin is effective in reducing the incidence and severity of pre-eclampsia in high-risk pregnancies. It is a safe, inexpensive, and accessible intervention that can significantly improve maternal and neonatal outcomes in the Pakistani population when introduced early in antenatal care.